Radiomics and deep learning from research to clinical workflow: neuro-oncologic imaging - Park, Ji Eun; Vollmuth, Philipp; Kim, Ho Sung (Korean journal of radiology, 2020)
Park JE, et al. Korean J Radiol. 2020 Oct;21(10):1126-1137. https://doi.org/10.3348/kjr.2019.0847
Gesehen am 14.10.2020